2017
DOI: 10.1016/j.jmps.2016.07.023
|View full text |Cite
|
Sign up to set email alerts
|

The chip-flow behaviors and formation mechanisms in the orthogonal cutting process of Ti6Al4V alloy

Abstract: A B S T R A C TThis work involves experimental and analytical investigations of chip flow stability in metal cutting process. First, in cutting experiments of Ti6Al4V alloy, the transformation of chip morphology from continuous to serrated and later to discontinuous was observed as the cutting speed increased. Scanning electron microscopic (SEM) observation of the shear fracture surface demonstrated shear-localized instability and intergranular failure behaviors. Then we used the improved orthogonal cutting mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(6 citation statements)
references
References 43 publications
(66 reference statements)
0
6
0
Order By: Relevance
“…Wang et al [94] studied the ductile-to-brittle transition in machining and found that as strain rate increased, chip morphology changed from the continuous to discontinuous types. Ma et al [95] carried out a high-speed orthogonal cutting experiment of TC4 on a modified SHPB and found that the brittle fracture occurred on the free surface of the chips. They also found that brittle fracture increased while ductile fracture decreased with an increase in cutting speed.…”
Section: Materials Embrittlement In Machining Processesmentioning
confidence: 99%
“…Wang et al [94] studied the ductile-to-brittle transition in machining and found that as strain rate increased, chip morphology changed from the continuous to discontinuous types. Ma et al [95] carried out a high-speed orthogonal cutting experiment of TC4 on a modified SHPB and found that the brittle fracture occurred on the free surface of the chips. They also found that brittle fracture increased while ductile fracture decreased with an increase in cutting speed.…”
Section: Materials Embrittlement In Machining Processesmentioning
confidence: 99%
“…Its mechanical framework, named as ASB onset system, was established by Wright and Batra in the 1980s [5]. The mechanical framework was subsequently modified by many researchers to define more applicable systems [6][7][8][9][10][11][12][13] for HSM. By applying appropriate boundary and initial conditions, these systems can be solved using numerical methods, such as the finite difference method.…”
Section: Introductionmentioning
confidence: 99%
“…By applying appropriate boundary and initial conditions, these systems can be solved using numerical methods, such as the finite difference method. Additionally, these systems can be handled by the perturbation method to establish ASB onset criteria [8,11,[13][14][15][16]. These criteria are convenient to assess if the ASB occurs under specific conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Yang et al [ 10 ] concluded that using a low cutting speed, large feed per tooth, and a large cutting depth could reduce the generation of saw-tooth-shaped cutting chips. Ma et al [ 11 ] experimentally analyzed the stability of chip flow in cutting Ti6Al4V alloy. It was observed that the chip morphology transformed from continuous to saw-tooth-shaped and then serrated cutting chips with the increase of cutting speed.…”
Section: Introductionmentioning
confidence: 99%